2021
DOI: 10.3389/fmars.2021.734066
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a Multipotent Component of Fish Feed: Basic Information for Its Potential Application in Aquaculture

Abstract: In vertebrates, melatonin (N-acetyl-5-methoxy-tryptamine, MEL) is synthesized from L-tryptophan (L-Trp), primarily in the pineal gland and additionally in several non-pineal tissues, including enterochromaffin cells of the gastrointestinal tract. The biosynthesis of MEL in the pinealocytes exhibits a daily rhythm with a nocturnal peak in synchronization with the dark phase of an environment. However, the temporal pattern of the gut melatoninergic system in fish is known to be synchronized with one or more non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 141 publications
0
5
0
Order By: Relevance
“…Quality of stored sperm was improved and shown to increase after melatonin administration (0.5µM) in paddle sh (Polyodon spathula) through the inhibition of ROS generation (Gao et al 2019). While there is scarcity of scienti c literature regarding seasonal oxidative status associated with melatonin concentration in testis in any sh, a very few experimental observations suggested its antioxidative role in protecting spermatozoa (Acharyya et al 2021). In addition of ROS, some researchers in mammalian studies suggested that nitrate (a form of NO), a useful marker of nitrosative stress, may stimulate spermatogenesis and the evidence in sh is supported by few studies (Wilson-Leedy and Ingermann 2011, Barman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of stored sperm was improved and shown to increase after melatonin administration (0.5µM) in paddle sh (Polyodon spathula) through the inhibition of ROS generation (Gao et al 2019). While there is scarcity of scienti c literature regarding seasonal oxidative status associated with melatonin concentration in testis in any sh, a very few experimental observations suggested its antioxidative role in protecting spermatozoa (Acharyya et al 2021). In addition of ROS, some researchers in mammalian studies suggested that nitrate (a form of NO), a useful marker of nitrosative stress, may stimulate spermatogenesis and the evidence in sh is supported by few studies (Wilson-Leedy and Ingermann 2011, Barman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The membrane of sh spermatozoa is particularly susceptible to ROS resulting impairment of its motility and fertility (Figueroa et al 2018;Len et al 2019). In order to mitigate cellular stress, a speci c defense system consisting of both enzymatic and non-enzymatic antioxidants aiming to establish a biological equilibrium with the generation of free radicals in testis (Acharyya et al 2021;Félix et al 2023). SOD coverts superoxide anion into hydrogen peroxide which is independently neutralized by heme-containing CAT, and selenium-containing GPx enzyme into water (Hasan et al 2014;Lu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that anti-stress effect of MEL can be mediated at different levels of the HPI axis. Bearing in mind the ability of MEL to cross the blood brain barrier ( 17 ), it is expected that this hormone reach neural sites of the HPI axis. Injections of CRH or ACTH increased cortisol in goldfish, which was not reversed by MEL pre-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin (MEL) is a neurohormone mainly synthetized in pineal gland and involved in several physiological activities in vertebrates including fish, playing a role in the adaptive behavior of the animal to the environment (16)(17)(18)(19). As a key signal in the regulation of circadian rhythms, MEL is related to many functions that have in common a rhythmic expression, such as feeding and locomotor activity (16,19).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (the sleep hormone) has been shown to inhibit feeding (e.g. goldfish [89]; zebrafish [90]; European seabass [91]), and affect digestive enzyme activities [92], suggesting that low melatonin levels might be responsible for increases in feeding and feeding efficiency. In pikeperch, Sander lucioperca [93] and goldfish [94], light colour does not affect food intake but blue light increases feed efficiency and growth rates.…”
Section: Effects Of Environmental Factors On Feedingmentioning
confidence: 99%